TMIC-42. LOCAL TISSUE METABOLOMICS BASED BIOMARKERS OF RESPONSE TO THERAPY FOR GLIOBLASTOMA. (11th November 2019) - Rajani, Karishma; Carlstrom, Lucas; Jacobs, Joshua; Schroeder, Mark; Olson, Ian; Wang, Xuewei; Sarkaria, Jann; Burns, Terry
Abstract: Glioblastoma (GBM) is a common deadly malignant brain cancer of the central nervous system (CNS), with a median survival of 12–15 months. Scientific advancements are lacking in developing effective therapies for both primary GBM, as well as secondary GBMs, that typically originate as malignant transformation of lower-grade isocitrate dehydrogenase (IDH) 1-mutant tumors. The unique metabolomic profile of IDH1-mutant tumors may present opportunities to develop biomarker signatures of therapeutic efficacy. Microdialysis is an extracellular fluid sampling collection technique utilizing a perfused semipermeable catheter to permit diffusion of molecules between brain interstitium and the perfusate. We hypothesized that microdialysis may identify a metabolomics-based biomarker response to therapy in IDH1-mutant tumors. To test this hypothesis, orthotopic xenografts were generated from two patient-derived GBM lines harboring mutations in IDH1. Perfusates were collected from intra-cranial tumors in aythmic nude mice sampled at baseline and 72h post treatment with temozolomide, an oral alkylating agent used to treat IDH1-mutant gliomas, compared with vehicle treatment, and TMZ-treated non-tumor bearing animals. Perfusates were analyzed via unsupervised metabolomic profiling using both gas and liquid chromatography-mass spectrometry (GC/LC-MS). Tumor specific metabolites such as carnitine and pyruvic acid were detected in microdialysate from tumor bearing mice compared to non-tumor bearing mice. Microdialysis is a feasible technology to identify metabolomics-based biomarker in IDH1-mutant PDX. This work is complemented by parallel analysis of non-IDH1-mutant and TMZ resistant xenografts to yield predictive in vivo tissue biomarkers of drug responsiveness translatable to clinical practice.